2020
DOI: 10.1002/ajcp.12427
|View full text |Cite
|
Sign up to set email alerts
|

Community Organizing and Transformative Change in the Response to Domestic Violence in India

Abstract: Pervasive cultural narratives that normalize domestic violence have made efforts to respond to domestic violence in India challenging. An effective response to domestic violence in India needs to be transformative in nature, supporting the empowerment of survivors of violence and empowering communities to support survivors. Various studies have highlighted the importance of settings like grassroots organizations for promoting empowerment of members through community organizing. This qualitative study builds on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…Archival data indicated that the agency had conducted meetings with 24,364 women and 15,340 men through community meetings. Additional details about the agency’s activities related to community engagement are described elsewhere (see Menon & Allen, in press). The present study focused on emerging counter narratives in the response to domestic violence.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Archival data indicated that the agency had conducted meetings with 24,364 women and 15,340 men through community meetings. Additional details about the agency’s activities related to community engagement are described elsewhere (see Menon & Allen, in press). The present study focused on emerging counter narratives in the response to domestic violence.…”
Section: Resultsmentioning
confidence: 99%
“…The field of community psychology has studied collaborations between agencies and communities, or community coalitions, as an effective vehicle for social change efforts, particularly among disenfranchised communities (e.g., Chavis, 2001). Thus, by effectively engaging and mobilizing community members in a collaborative manner (see Menon & Allen, in press) and empowering them through community participation, the agency is able to facilitate the creation of a community that upholds counter narratives that are supportive to survivors of violence and takes on collective responsibility in this area. This approach is unique in its recognition that changes at the individual level (e.g., working with survivors alone), without accompanying shifts in community contexts are not likely to be sustainable (Maton, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations